Process safety management and the electrical function - Wellman, C.M.; McConnell, J.D. (Record of Conference Papers. IEEE Industry Applications Society 44th Annual Petroleum and Chemical Industry Conference, 1997)
OSHA regulations mandating process safety can have a significant impact on the full life cycle of an electrical system. Implementation of process safety management (PSM) is intended to prevent catastrophic accidents. It includes powerful managing system elements that can be applied to improve electrical safety and help meet other business objectives. This paper introduces the subject and discusses how to apply PSM to electrical facilities in plants.